Ketolide antibiotics: will they ever be used for community-acquired pneumonia? - Metersky, Mark L.; Huang, Yi (Annals of Research Hospitals; Vol 1 (April 2017): Annals of Research Hospital, 2017)
There is no perfect antibiotic for community-acquired pneumonia (CAP). β-lactams do not cover atypical organisms, most importantly, Legionella. Fluoroquinolones remain active against Streptococcus pneumoniae and cover atypical bacteria, but are associated with serious side effects including tendon rupture and a variety of neurologic side effects.